Safety Assessment of Ocimum Basilicum Hydroalcoholic Extract in Wistar Rats: Acute and Subchronic Toxicity Studies - Rasekh, Hamid Reza (Mashhad University of Medical Sciences, 2012)
OBJECTIVE(S): Ocimum basilicum L. is widely used in folk medicine of many countries including . Both O. basilicum and its oil extract have received considerable attention for their potential medicinal properties, but there are a few reports about possible toxicity of this plant. Therefore, in the present study, acute and subchronic toxicity of O. basilicum hydroalcohlic extract have been evaluated in Wistar rats. MATERIALS AND METHODS: For the acute toxicity assessment, five groups of 10 animals (5 male, 5 female) received four different single dose of extract orally, the animals were, then, kept under observation for 14 days. For subchronic toxicity, the animals were divided into four groups (5 male, 5 female) and were gavaged daily by 50, 200 and 500 mg/kg of extract. Mortality, clinical signs, body weight changes, food and water consumption, and hematological and biochemical parameters were monitored during the study period. On the 45th day, animals were sacrificed and gross findings, weight of liver and left kidney and liver histological markers were assessed. RESULTS: The results of acute study indicated that LD(50 )of O. basilicum is higher than 5 mg/kg. In subchronic study, no adverse effects were observed on serum parameters in male and female rats. The hematological results showed a reduction in the hematocrit, platelets and RBC in both sexes. No abnormalities were observed in other parameters. CONCLUSION: Based on the results of this study, present data suggest that hematologic system could serve as a target organ in oral toxicity of this plant.